A PROPOSAL TO CREATE A TOURIST INFORMATION SYSTEM FOR URALSK. THEORY AND PRACTICE - Dąbrowski, Dariusz (Вестник ЗКУ, 2022)
The policy of the Kazakh government focuses on increasing the role of tourism in the entire country, also in its individual regions, including events dedicated, in particular, to cultural heritage and methods of its popularization. Uralsk is a city with a rich and diverse resource of relics of the past, both in the field of material and non-material culture. This applies to the architectural and town-planning complex of the city itself, as well as to such values and phenomena as: folklore and customs of the peoples living in Uralsk and its environs, i.e. mostly Kazakhs and Yaik Cossacks (and - to a lesser extent - others), as well as, for example, a collection about famous people who were associated with this city. Interesting objects from a historical and cultural point of view are also located at a short distance from the city itself. For example, the remains of the city of the Golden Horde called "Zhaiyk". The theory and practice of creating and disseminating knowledge about cultural heritage using a tourist labeling system is important from a historical point of view for creating a widely understood permanent designation system in Uralsk, which will be discussed later in the article.